Pelatihan Pembuatan Kompos Blok Berbasis Limbah Ternak Sapi dan Limbah Kopi: Strategi Zero Waste dan Perbaikan Sifat Fisik Tanah Berpasir di Kebun Kopi Desa Bambang, Malang: Training on Making Block Compost Based on Cattle Waste and Coffee Waste: Zero Waste Strategy and Improvement of Physical Properties of Sandy Soil in Bambang Village Coffee Plantation, Malang - Siswantoro, Ajik; Kurniawan, Irvan; Eka Hardana, Andrea; Alfiani, Firda (Fakultas Pertanian Universitas Brawijaya, 2025)
Bambang Village, which is geographically located in Wajak District, Malang Regency, is known to have a prominent dual economic potential, namely from the coffee plantation and cattle farming sectors. Despite its high economic potential, Bambang Village is faced with two interrelated agronomic and environmental issues. Block Compost is a specific, efficient, simple, but highly efficient technological innovation. The implementation of Block Compost adopts a Circular Economy or Zero Waste approach. In the context of agronomic applications, Block Compost has proven to be very effective on lands with extreme environmental conditions, such as sandy lands, post-mining land, and locations with low rainfall. The community service program through training in making Block Compost in Bambang Village, Wajak District, Malang Regency, succeeded in overcoming a double problem, namely the accumulation of cow feces waste and the degradation of the physical properties of sandy soil in people's coffee plantations. This program creates a zero-waste solution that integrates the livestock and agricultural sectors, while providing economic added value through the conversion of waste into fertilizer products with selling value, thereby supporting the economic independence of the village.